Twist extrusion - Beygelzimer, Y.; Varyukhin, V. (Физика и техника высоких давлений, 2014)
The work presents the results of research and development on Twist Extrusion (TE) process. It was shown the two main deformation zones of TE are located at the two ends of the twist part of the die. The mode of deformation in these zones is simple shear in the transversal layers, as in high pressure torsion (HPT). In terms of strain, at the first approximation, the billet during TE like passes through two “transparent” HPT anvils. TE has a significant commercial potential due to the following physical effects: intensive grain refinement; homogenization and mixing; intensive powders consolidation. There are three main areas in TE application for the present: formation the submicron and nanostructures in the bulk metals samples; processing of the recycled non-ferrous metals and alloys for the improvement of the mechanical properties; production the bulk samples through powders consolidation. Donetsk Institute for Physics and Engineering created a TE Center to showcase the process and educate investors. Our experience with the center has shown that the most prospective directions are producing ultrafine-grained alloys for medical and aircraft applications. Представлены результаты исследований процесса винтовой экструзии (ВЭ) и разработок по его осуществлению. Показано, что основная деформация материалов при ВЭ происходит в двух зонах простого сдвига, расположенных по границам винтового участка матрицы. ВЭ имеет значительный коммерческий потенциал благодаря быстрому измельчению зерен и интенсивному массопереносу, приводящему к гомогенизации и перемешиванию материалов. В настоящее время наметились три основных направления в применении ВЭ: формирование субмикронных и наноструктур в металлах и сплавах; обработка вторичных цветных металлов и сплавов для улучшения их механических свойств; производство объемных образцов путем консолидации порошков. Донецкий физико-технический институт создал опытный участок ВЭ, чтобы продемонстрировать процесс и привлечь инвесторов. Опыт работы этого участка показал, что наиболее перспективным направлением применения ВЭ является производство субмикрокристаллических материалов для медицины и авиации.